Masculinity and Immigrant Health Practices: How Male Kurdish Immigrants to the United States Think about and Practice Health - Othman, Jihad K.; Linders, Annulla (Qualitative Sociology Review, 2018)
Researchers have identified a host of factors that influence immigrant men’s understanding of and commitment to health, but overall the scholarship is still unsettled, in large part because the experiences of immigrant groups are so varied. In this paper, based on interviews with Kurdish immigrants in the United States, we demonstrate that the field of health provides both opportunities and pitfalls for men whose social, familial, and masculine aspirations simultaneously pull them into American life and push them towards a segregated existence. We conclude that men use a discourse of health to simultaneously assert themselves as men and maintain their connections to their original culture, just as they use a discourse of masculine responsibility to account for the health-related choices they make.